Design and Development of a Microcontroller-Based Automatic Chicken Feeder - Mansur, Maulana (Institut Teknologi Adhi Tama Surabaya, 2025)
The use of technology such as automatic feed management systems helps create convenience in feeding chickens regularly and optimally for chickens, most village chicken farmers have other activities such as work, etc. therefore farmers can be negligent or forget to feed their livestock, due to this problem, many farmers fail to raise livestock. That is why the idea was born to make an automatic chicken feed system based on the ESP8266 microcontroller that can provide feed for chickens automatically and regularly. This system uses the RTC (real time clock) conveyor as a timer input to run the system, after a predetermined time the ESP8266 will command the DC motor to rotate the spiral screw which will carry the feed from the hoper to the 3 containers where in the test results the feeding time for 3 minutes 40 seconds produces 700grams of feed where the first container contains 300grams, the second container 200grams and the third container 200grams.